Urban Women, Their Religion, and Response to Environmental Crisis: Empirical Evidence in Green School and Majlis Taklim Ulin Nuha - Maghfur Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study argues against the thesis that environmental crisis occurring today is due to masculine men’s domination over women in managing natural resource. Through an in-depth analysis on environmental conservation movement conducted by women in Pekalongan City, this study is projected to be antithesis on feminist’s perspective on the response to environmental crisis issue. This research focuses on the environmental action in religion and gender’s perspective in Green School and Majelis Taklim Ulin Nuha communities. Methodologically, data of this case study research was obtained through observation, interview, and documentation. The result of research shows that the ideology of environmental conservation has diverse paradigms: developmentalistic, constructivistic, and emancipatory. In the context of movement issue and model, urban women’s action in the research location also provided various topics: education, economics, and social movement, by involving school institution, majelis taklim, and non-government organization (NGO). Urban women in Pekalongan make religion and expedient technology the basis for resolving environment crisis by integrating masculinity into femininity harmoniously.